2011
DOI: 10.1002/jms.2002
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization and dissociation of the monoterpene limonene: mass spectrometric and computational investigation

Abstract: The photoionization of the monoterpene limonene has been studied using tunable vacuum ultraviolet synchrotron radiation in the region from the threshold for ionization of the parent molecule up to 15.5 eV. The adiabatic ionization energy of limonene is derived from photoionization efficiency spectrum and found to be 8.27 eV, compared with the density functional theory calculations which yields a value of 8.08 eV (B3LYP/6-311++G). Primary dissociation pathways of the parent molecule ions are investigated by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
12
2
Order By: Relevance
“…As seen in Figure , at 10.0 eV there are very weak (≪1 %) peaks at 93/95 amu and 121 amu. The complete lack of fragmentation for h ν≤9.5 eV contrasts with our own earlier photoionization studies of limonene and the more recent molecular beam work of Fang et al . which both show more significant amounts of “94” amu, 121 amu, and other fragment masses, all with apparent onsets in the 9–9.3 eV region.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…As seen in Figure , at 10.0 eV there are very weak (≪1 %) peaks at 93/95 amu and 121 amu. The complete lack of fragmentation for h ν≤9.5 eV contrasts with our own earlier photoionization studies of limonene and the more recent molecular beam work of Fang et al . which both show more significant amounts of “94” amu, 121 amu, and other fragment masses, all with apparent onsets in the 9–9.3 eV region.…”
Section: Resultscontrasting
confidence: 99%
“…Using B3LYP/6–311++G calculations Fang et al . are able to suggest relatively low thermodynamic thresholds for m / z 94 and m / z 121 dissociation channels, but with transition states that create significant kinetic barriers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fang et al used VUV photoionisation in a single-particle aerosol time-of-flight mass spectrometer (ATOFMS) for characterisation of the composition of SOAs produced through photooxidation of toluene in a smog chamber. [48,49] Robinson et al [50] reported coupling of a softer ionisation source with an Aerodyne aerosol mass spectrometer (AMS). In that study, a metastable atom bombardment (MAB) ionisation source was incorporated so the system could be readily switched between MAB and traditionally used electron ionisation (EI).…”
Section: Online Ms Methodsmentioning
confidence: 99%